The Data-Driven Economy. Remarks in the Light of Selected Issues in the Competition Law - Jacolik, Magdalena (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
Data has begun to play a vital role in global, EU-wide and domestic economies. On 19 February 2020, the European Commission published the EU’s strategy for data, which outlines a new and unprecedented approach to development. The vision thus described – a data-driven economy – is to be implemented within the next five years.However, this broad undertaking gives rise to a number of legal, economic and social issues which deserve to be more thoroughly examined. In this paper, the author considers how the data economy relates to aspects of competition law, including threats associated with the sharing of confidential company data, and information protected under intellectual property laws, among the participants of the market economy, i.e. businesses. Also, observations are made concerning the hypothetical emergence of monopolies and oligopolies, as well as collusive agreements between enterprises on the grounds of the new approach to development.